Brazil Low Carbon Country Case Study - World Bank (Washington, DC, 2014)
Brazil low carbon country case study was two years in the making based on a study by the World Bank assisted by the United Nations Development Program (UNDP) and the Energy Sector Management Assistance Program (ESMAP). It supports Brazil's integrated effort towards reducing national and global-emissions GHG while promoting long-term development. It builds on the best available knowledge and is underpinned by a broad consultative process and survey of available literature. The study was coordinated by Christophe de Gouvello, a Senior Energy Specialist in the Sustainable Development Department of the Latin American and the Caribbean Region. The study's scope was discussed with the Ministries of Foreign Affairs, Environment and Science and Technology, as well as representatives of the Ministries of Finance, Planning Agriculture, Transport, Mines and Energy, Development, Industry and trade. More than 15 technical reports and 4 synthesis reports have been commissioned in the course of this work. For a quick overview of priority issues, analysis is presented using reader-friendly charts, graphs, and annotations organized in chapters according to the four key emission sectors, land use, land-use change, and forestry (LULUCF), including deforestation; energy production and use, particularly electricity, oil and gas and bio-fuels; transport systems; and solid and liquid urban waste.